The cIMPACT-NOW updates and their significance to current neuro-oncology practice - Gonzalez Castro, L Nicolas (Neurooncol Pract, 2020)
Over the past 4 years, advances in molecular pathology have enhanced our understanding of CNS tumors, providing new elements to refine their classification and improve the 2016 World Health Organization (WHO) Classification of CNS tumors. The Consortium to Inform Molecular and Practical Approaches to CNS Tumor Taxonomy—Not Official WHO (cIMPACT-NOW) was formed in late 2016 by a group of neuropathology and neuro-oncology experts to provide practical recommendations (published as cIMPACT-NOW updates) to improve the diagnosis and classification of CNS tumors, in advance of the publication of a new WHO Classification of CNS tumors. Here we review the content of all the available cIMPACT-NOW updates and discuss the implications of each update for the diagnosis and management of patients with CNS tumors.